Pengaruh Pemanfaatan Media Youtube Terhadap Keterampilan Menulis Cerpen - Sobri Sobri; Tatu Hilaliyah; Ilmi Solihat; Imam Safi'i (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This article aims to describe the effect of using Youtube media on the ability of fifth graders at SDN Gerem 1 Cilegon City in writing short stories. The method used in this research is the True Experimental Design method using the Pretest-Posttest Control Group Design research design. The results showed that the use of Youtube media had a significant effect on students' ability to write short stories. The results of the experimental class pretest before getting treatment using Youtube media an average value of 59.5. The results of the short story writing skills test after getting treatment using Youtube media the average value of 80.16.